2009
DOI: 10.1111/j.1365-2141.2009.07714.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus can make immune thrombocytopenic purpura refractory

Abstract: SummaryImmune thrombocytopenic purpura (ITP) is characterized by decreased platelet numbers secondary to platelet destruction and reduced platelet production. Even if the ITP persists, it typically responds to 'ITP-specific' therapies, such as intravenous immunoglobulin, steroids, intravenous anti-D, and splenectomy. Several reports, including our previous study, have implicated cytomegalovirus (CMV) in the pathogenesis of infrequent cases of ITP that were not severe in nature. A recent study from China sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 45 publications
5
89
0
4
Order By: Relevance
“…Regarding platelet count, Patient 3 showed marked thrombocytopenia of 2 × 10 9 /L, possibly being immune thrombocytopenic purpura as previously reported [13], which was later resolved with immunosuppressive therapy. The median percentage of atypical lymphocytes was 21.3%, ranging from 19.0 to 36.9%.…”
Section: Laboratory Findings Of Cmv-im Patientssupporting
confidence: 53%
“…Regarding platelet count, Patient 3 showed marked thrombocytopenia of 2 × 10 9 /L, possibly being immune thrombocytopenic purpura as previously reported [13], which was later resolved with immunosuppressive therapy. The median percentage of atypical lymphocytes was 21.3%, ranging from 19.0 to 36.9%.…”
Section: Laboratory Findings Of Cmv-im Patientssupporting
confidence: 53%
“…Finally, direct binding of Mycoplasma to the platelets, generating a complex that is then recognized as foreign by the immune system, might be another option. Whatever the mechanism would be, a special behavior of a subset of ITP caused by a certain organism is an intriguing option, as was suggested recently for ITP triggered by CMV infection [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, a combination of both IV ganciclovir and IV cytogam had been used to optimize rapid suppression of the CMV. 5 The same study showed that use of steroids and other immunosuppressive treatment may exacerbate the primary CMV infection and worsen the ITP, or at least prevent it from improving. Also of interest is that, when CMV is controlled by anti-viral therapies, normal treatments for ITP, such as IVIG and splenectomy regain their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Also of interest is that, when CMV is controlled by anti-viral therapies, normal treatments for ITP, such as IVIG and splenectomy regain their effectiveness. 5 The response rate of platelet counts following treatment of CMV has seen to vary widely between studies.…”
Section: Discussionmentioning
confidence: 99%